ANALISIS KEMAMPUAN LAHAN PADA SATUAN WILAYAH PENGEMBANGAN DI KOTA AMBON - Lasaiba, Mohammad Amin; Tetelepta, Edward Gland; Riry, Roberth Berth; Lasaiba, Irvan (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Optimizing land use plans is carried out for land capabilities that are useful for conserving land resources so that they can reduce the problem of land degradation. This study aimed to assess the level of land capacity and determine the function of both protected and cultivated areas in Development Area Units (SWP). The method used in the research is quantitative descriptive, consisting of data collection and processing stages. Data collection was carried out through literature studies from several related agencies. Meanwhile, spatial data analysis was carried out using Geographic Information System (GIS) software. The results of the research showed that the analysis of land capacity, especially for determining the function of areas for settlement, reached 3,687.35 ha and the buffer area was around 11,755.27 ha. This indicates that only a small portion of suitable areas can be developed for urban development. This is due to the physical limiting factors of the land where the characteristics of the Ambon City area are dominated by hilly areas.